Multiplexed on-chip real-time PCR using hydrogel spot array for microRNA profiling of minimal tissue samples - Jung, Seungwon; Kim, Bong Kyun; Lee, Sangjoon; Yoon, Seungmin; Im, Heh-In; Kim, Sang Kyung (ELSEVIER SCIENCE SA, 2018)
Since microRNAs (miRNAs) have been considered as regulators of messenger RNA ( mRNA) translation, the development of the simple, multiplex, and quantitatively precise miRNA profiling techniques becomes more significant. Here, an on-chip multiplex real-time quantitative polymerase chain reaction (qPCR) for miRNA profiling is demonstrated with a primer-immobilized network (PIN) array, which consists of hundreds of hydrogel spots. The array renders highly dense reaction cells of 20 x 20 in 1 cm(2). Uniform performance of the 400 real-time PCR reservoirs was achieved through our fabrication process. The amplicons and their fluorescent signals were isolated in each hydrogel spot, whose detection limit was measured to 16 aM, covering a seven-log concentration range. With the PIN spots of different primers, multiple miRNAs could be quantified in a single reaction out of very limited amount of RNA. For proof of concept, ten different miRNAs from the medial habenula of a mouse which is small region of the brain were successfully analyzed. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: GENE-EXPRESSION MEASUREMENTS; SYSTEM; CDNA